Applied health economics - Jones, Andrew M., 1960- (New York : Routledge, 2013)
'The first edition of Applied Health Economics did an expert job of showing how the availability of large scale data sets and the rapid advancement of advanced econometric techniques can help health economists and health professionals make sense of information better than ever before.The book draws on key sources of information such as the European Community Household Panel (ECHP) and the WHO Multi-Country Survey Study (WHO-MCS) and assumes a familiarity with the computer programme Stata, now in an eleventh version. The book has been fully updated to reflect the enhancements to this key package.In addition to methodology, the book also contains a brand new chapter on regression models for health care costs, thus broadening the book's readership to those working on risk adjustment and health technology appraisal. The text also fully reflects the very latest advances in the health economics field and the key journal literature'--Provided by publisher.
Data and survey design -- Describing the dynamics of health -- Describing health care costs -- Reporting heterogeneity in health -- Health and lifestyles -- Smoking and mortality -- Health and retirement -- Health and wages -- Modelling the dynamics of health -- Non-response and attrition bias -- Models for count data -- Modelling health care costs.
Includes bibliographical references (p. [381]-387) and index.
Keywords: Economics, Medical; Health Care Costs; Statistics as Topic